Hubungan Efikasi Diri dan Kesiapan Belajar pada Mahasiswa Pasca Pandemi - Andra Rosita Afandi; Iin Ervina; Anggraeni Swastika Sari (Jurnal Psikologi, 2023)
Learning readiness is the overall readiness of a person to react or respond to a situation in a certain way, according to Slameto (Harmini, 2017). In order for students to have optimal learning readiness, self-efficacy is needed. The aim of this research is to determine the relationship between self-efficacy and learning readiness among Muhammadiyah University of Jember students after the pandemic. This type of research is quantitative correlational. The population is 11,200 Muhammadiyah Jember University students with a sample of 336 students. The sampling technique uses simple random sampling using student NIM. Data collection uses Google Form and is carried out directly by distributing questionnaires in paper form. The scale used is a self-efficacy scale adapted from research by Siti Sundari (2022) with validity test results of 37 valid items and a Cronbach's Alpha value of 0.947. The learning readiness scale was adapted from research (Sari, 2020) with validity test results of 30 valid items with a Cronbach's Alpha value of 0.918. The results of this study indicate that there is a significant positive relationship between the self-efficacy variable (X) and the learning readiness variable (Y) of ( r = 0.759 ; p < 0.05). This means that the higher the student's self-efficacy, the higher the student's learning readiness to learn, and conversely, the lower the student's self-efficacy, the lower the student's learning readiness to learn.